TAS-102 in combination with bevacizumab for second-line treatment of metastatic colorectal cancer with a hypertensive elderly patient: a case report - Xu, Lingling; Qiu, Xun; He, Hongmei; Liu, Lili; He, Qing; Sun, Jinghua (Frontiers in Oncology, 2025)
BackgroundColorectal cancer (CRC) is a common malignant tumor worldwide. Approximately 20%–25% of patients have metastases at the time of initial diagnosis, and nearly half eventually develop metastatic cancer. The standard first- and second-line treatments for unresectable metastatic CRC are full-dose two-/three-agent chemotherapy with or without a combination of molecularly targeted agents. However, many patients are ineligible for intensive therapy due to poor performance status or advanced age. TAS-102 (trifluridine/tipiracil) in combination with bevacizumab may provide a new treatment strategy for patients with advanced CRC who are ineligible for intensive therapy.Case report descriptionWe report a case of a 91-year-old woman diagnosed with stage IV adenocarcinoma of the rectosigmoid junction in the presence of multiple metastases. The patient had a history of hypertension, had suffered from deep vein thrombosis of the left lower extremity, and was allergic to several drugs. Genetic testing showed multiple mutations in Kirsten Rat Sarcoma Viral Oncogene Homolog (KRAS), Phosphatidylinositol-4,5-bisphosphate 3-Kinase Catalytic Subunit Alpha (PIK3CA), and Tumor Protein p53 (TP53); microsatellite stability; and a tumor mutational burden of 4.5 Mut/Mb. The patient was diagnosed with stage IV adenocarcinoma of the rectosigmoid junction in May 2020, with a clinical stage of cTxNxM1. Without surgery, the patient received first-line treatment with capecitabine in combination with bevacizumab, which was changed to second-line treatment with TAS-102 in combination with bevacizumab after disease progression, with a progression-free survival of 10 months, achieving a significant survival benefit. Later, due to the patient’s poor physical condition, no further medication was administered, and the patient died on 1 September 2022.ConclusionTAS-102 in combination with bevacizumab for the treatment of elderly patients with metastatic CRC who are ineligible for intensive therapy is a promising treatment option.